Manajemen Dana Bantuan Operasional Sekolah Menengah Pertama Negeri 10 Kecamatan Sirimau Kota Ambon - Latupeirissa, Rivando; Wenno, I H; Rahabav, P (LP. Ma'arif Janggan Magetan, 2023)
his study aims to determine the management of School Operational Assistance (BOS) funds at SMP Negeri 10 Ambon. This research used a descriptive qualitative method with data collection techniques using in-depth interviews, observation and documentation. This research involved the school principal and BOS treasurer as primary data sources. Secondary data sources included school profile, vision and mission, BOS Annual Activity Plan (Rencana Kerja Tahunan-RKT), BOS Accountability Report (Laporan Pertanggung Jawaban-LPJ), and teacher data. The interview results were then transcribed into Bahasa Indonesia. The results showed that the management of BOS funds went through several stages and processes, namely planning, management, evaluation and reporting. The components of planning, management, evaluation and reporting showed that SMP Negeri 10 Ambon had run well in accordance with the technical guidelines for the management of BOS funds, except for the lack of trust and transparency by the managers to each field related to BOS funds. In this study, there were several obstacles, namely delays in fund disbursement, lack of transparency in terms of budget implementation, and accountability problems in reporting management and evaluation. The obstacles found resulted in the regulation carried out by schools being hampered so that the program that had been prepared in the RKAS could not run properly. Recommendations that can be given are that periodic evaluations from stakeholders can continue to be conducted for effective and efficient regulation of BOS funds.